2013
DOI: 10.1007/bf03354885
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Spatially Non- Stationary Associations Between the Second Demographic Transition and Infant Mortality: A Poisson GWR Approach

Abstract: Based on ecological studies, second demographic transition (SDT) theorists concluded that some areas in the US were in vanguard of the SDT compared to others, implying spatial nonstationarity may be inherent in the SDT process. Linking the SDT to the infant mortality literature, we sought out to answer two related questions: Are the main components of the SDT, specifically marriage postponement, cohabitation, and divorce, associated with infant mortality? If yes, do these associations vary across the US? We ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The GWGR model is simple and commonly used in the related studies about this issue [26]. In order to compare our result to similar studies, and also for convenience consideration, we decided to use GWGR as the basis for our new SD-GTWR model.…”
Section: Construction Of the Seasonal Difference-geographically Anmentioning
confidence: 99%
“…The GWGR model is simple and commonly used in the related studies about this issue [26]. In order to compare our result to similar studies, and also for convenience consideration, we decided to use GWGR as the basis for our new SD-GTWR model.…”
Section: Construction Of the Seasonal Difference-geographically Anmentioning
confidence: 99%
“…Although demographers have recently begun to recognise spatial contingencies in the factors underlying contemporary fertility variation (Işik & Pinarcioğlu, ; Vitali & Billari, ; Yang, Shoff, & Matthews, ), it remains a riddle whether similar spatial heterogeneity could be identified for earlier periods of human history and in other domains of demographic behaviour. In this paper, we set out to explore this possibility by seeking to answer three interrelated questions: Did the relationships between the share of elderly people living without kin in historic Europe and aggregate contextual factors vary significantly over space?…”
Section: Introductionmentioning
confidence: 99%
“…This literature provides a strong argument in favour of considering the spatially contingent relationships among the explanatory and dependent variables in demographic research. Several recent papers have picked up this agenda revealing substantial spatial heterogeneity in the association between fertility and its correlates (Işik & Pinarcioğlu, ; Yang et al, ; Vitali & Billari, ). However, a corresponding, spatially sensitive inquiry into the pan‐European diversity of elderly residential patterns and their determinants remains to be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Hadayeghi et al [5] showed that the GWPR models are useful for capturing spatially dependent relationships and generally performing better than the conventional Generalized Linear Model. Yang et al [9] applying GWPR to investigated the relationship of marriage postponement, cohabitation rates and divorce rates with infant mortality in the US.…”
Section: Introductionmentioning
confidence: 99%